Rapid de-escalation of anti-MRSA therapy guided by S. aureus nares screening for patients with pneumonia: protocol of a randomized controlled trial (SNAP study) - De Vita, Elda; Segala, Francesco Vladimiro; Cavallin, Francesco; Guido, Giacomo; Frallonardo, Luisa; Cotugno, Sergio; Pellegrino, Carmen; Di Gennaro, Francesco; Saracino, Annalisa (Frontiers in Medicine, 2024)
Introduction The current Infectious Disease Society of America and American Thoracic Society (IDSA/ATS) guidelines recommend linezolid or vancomycin as an empiric treatment for methicillin-resistant Staphylococcus aureus (MRSA) pneumonia in hospitalized patients with specific risk factors,. A nasal PCR-assay for MRSA, with its high negative predictive value, can guide a rapid antibiotic de-escalation avoiding unnecessary anti-MRSA treatment. The indiscriminate use of these drugs has contributed to the emergence of resistant S. aureus strains leading to adverse effects without any survival benefit, increasing hospital stays and associated costs. Aim of the study is the use of this diagnostic tool to reduce empirical anti-MRSA treatment duration in pneumonia, shortening antimicrobial therapy days while measuring in-hospital mortality, length of stay and adverse drug event incidence. Methods It is a prospective, randomized single-center controlled trial planned to be conducted in the Azienda Consorziale Policlinico di Bari. The research project will have a duration of 12 months following the approval of the Ethical Committee of the University of Bari. The minimum sample size is 38 patients per group, for a total of 76 subjects, calculated assuming a standard deviation of 10, a power of 90%, a type I error of 5% and a 10% drop-out rate. We will enroll eligible patients ensuring their evidence-based management according to guidelines, we will perform a nasal swab for MRSA in patients in the experimental group and discontinue the empirical anti-MRSA therapy if the nasal swab result is negative. For both arms, follow-up visits will be on day 2, 5, 7, 14, and 28 relatives to the enrollment visit (day 0). Data will be collected on the clinical course of pneumonia and laboratory tests. Discussion Our study will provide evidence on the duration (in days) of the antibiotic intake as a primary outcome of the study. Secondary outcome measures include in-hospital mortality, the length of stay and days of mechanical ventilation (in VAP), and the incidence of adverse events related to the administration of the therapy. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/NCT06238297, identifier NCT06238297.